COOKING OIL PRICE CONTROL POLICY IN INDONESIA (A review of Ibn Taimiyah's thoughts) - Eva Nurul Huda; Sahabudin Sidiq (Reinforce: Journal of Sharia Management, 2023)
This study aims to analyze cooking oil price control policies in Indonesia by examining Ibn Taimiyah's thoughts about market mechanisms and price interventions. The research method used is a qualitative research methodology with a literature study approach. The research results show that the market mechanism in Islam is free of any intervention. However, the government can intervene in market prices when distortions occur. The government's policy of providing cooking oil subsidies to the less fortunate and setting the lowest retail price is permissible because there are conditions where producers do not want to sell their goods except at a price higher than the general market price, even though consumers really need these goods. According to Ibnu Taimiyah, the government may intervene in prices and limit sales after conducting negotiations, discussions, and consultations with interested communities.